2002
DOI: 10.1097/00001721-200209000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Activation of factor IX by erythrocyte membranes causes intrinsic coagulation

Abstract: As an extension of our earlier work, procoagulant activity of erythrocyte [red blood cell (RBC)] membrane was examined using biochemical and rheological techniques. Western blot analysis of coagulation factors incubated with erythrocytes (RBCs) showed that only factor IX (FIX) was activated by RBC membranes in the presence of calcium ions. A fluorogenic assay suggested that activated FIX is capable of activating factor X. A preliminary crude extraction of the substance from RBC membranes suggested that a FIX-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 34 publications
4
35
0
Order By: Relevance
“…Nevertheless, some investigators have demonstrated the initiation of the coagulation cascade by phospholipids and Factor XI on erythrocytes, even in the absence of tissue factor, 49 which may be relevant to our present results. In any case, further investigations are required to elucidate the correct mechanism of the initiation of the activation of the coagulation cascade on the surface of the platelet thrombi under blood flow conditions.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Nevertheless, some investigators have demonstrated the initiation of the coagulation cascade by phospholipids and Factor XI on erythrocytes, even in the absence of tissue factor, 49 which may be relevant to our present results. In any case, further investigations are required to elucidate the correct mechanism of the initiation of the activation of the coagulation cascade on the surface of the platelet thrombi under blood flow conditions.…”
Section: Discussionsupporting
confidence: 72%
“…Regulatory role of platelet-derived procoagulant activity on the continuous activation of platelet and thrombus growth. Platelets, once they interact with subendothelial matrix such as collagen or von Willebrand factor (VWF), 48,49 activated to release ADP-containing dense granules. Next, the released ADP stimulates ADP receptors (P2Y1 and P2Y12).…”
Section: Discussionmentioning
confidence: 99%
“…To determine which factor (i.e., F-IX or F-X) was activated by RBCs, Western blot analysis of F-IX and F-X incubated with washed normal human RBCs was performed [12]. A band corresponding to activated F-IX (F-IXa) appeared (Fig.…”
Section: Coagulation Factor Activation Assaymentioning
confidence: 99%
“…However, clinical evidence to support the view that markedly reduced venous flow directly induces the initiation of thrombus formation at an intact vessel wall remains contradictory [9,10]. In our previous papers [11][12][13][14], it was shown that the coagulation reaction initiated through a direct activation of F-IX by an enzyme on RBC membranes serves as a triggering mechanism for pathogenesis of venous thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Dehydration increases the hematocrit and blood viscosity both of which could induce thrombotic tendency [4]. Moreover, elevated hematocrit levels are reported to promote activation of factor IX (an intrinsic factor for coagulation cascade) by erythroelastase IX (factor IX-activating enzyme) in erythrocytes, which could further enhance the coagulation pathway [5,6]. In addition, patients with reduced renal function are more likely to develop pulmonary thromboembolism than those with normal kidney function [7].…”
Section: Discussionmentioning
confidence: 99%